2007
DOI: 10.1002/jbm.b.30837
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the hybrid layer on the bond strength of restorations subjected to cyclic loading

Abstract: The present study evaluated the long-term microtensile bond strength of collagen-depleted dentin followed by cyclic loading. Bovine flat, midcoronal dentin received one of the following surface treatments: acid-etch or acid-etched + 5% NaOCl for 2 min. The teeth were restored with Single Bond, Scotchbond Multi-purpose, One-Step Plus, or All-Bond 2 adhesive systems. Half of the specimens were randomly assigned to receive 200,000 cycles (50 N force). Teeth were sectioned into 1 x 1 mm thick slices and stored for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…The total depth of dentin demineralization is not fully infiltrated by monomers, which leaves an exposed collagen network, susceptible to hydrolytic degradation over time [9]. The removal of dentin matrix, the so-called deproteinization, has already been proposed as a possible treatment to increase bond strength longevity and decrease technique sensitivity [7, 22]. However, a long-term study revealed decrease in the deproteinized dentin-resin bonds [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The total depth of dentin demineralization is not fully infiltrated by monomers, which leaves an exposed collagen network, susceptible to hydrolytic degradation over time [9]. The removal of dentin matrix, the so-called deproteinization, has already been proposed as a possible treatment to increase bond strength longevity and decrease technique sensitivity [7, 22]. However, a long-term study revealed decrease in the deproteinized dentin-resin bonds [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, a long-term study revealed decrease in the deproteinized dentin-resin bonds [22]. In addition, the HL is believed to be important as a stress-buffering layer under mechanical loading [7]. Thus a stronger, stable, and resistant collagen layer is more suited substrate for current dental adhesive restorations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of the chemostat-based biofilm fermentor in this study was based on our group's previously established non-destructive experimental model (21), which was subsequently adapted for assessment of the interface of root canal sealers with root dentin in simulation of intraoral pathogenic conditions (22). Unlike in the previous studies (24, 25), bovine roots were used in the current study, because their large canals facilitated standardized application of surface treatments with CSRB and PHCS. Also, the large canals could be bored to produce parallel walls, in order to maximize the focal depth of CLSM while accounting for the transparency of materials (26).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports stated that this adhesive is not capable of effectively filling the pores created by the sodium hypochlorite because its slow diffusion [35,36]. For etch-and-rinse adhesives, such as Single Bond 2, the hybrid layer represents the principal mechanism of adhesion [37][38][39]. Therefore, the presence of collagen is pivotal.…”
Section: Os Lo Os Lo Os Lo Os Lomentioning
confidence: 99%